Clinical use of a betamimetic (Orciprenaline) in Obstetrics (Preliminary Communication) - Yanque Montufar, Ramiro (2015)
Orciprenaline, a beta-adrenergic agent, in 48 cases of obstetric pathology and 12 women in normal labor is used. At the doses of 10 to 20 micrograms per minute, the Orciprenaline inhibited uterine contractility in 59 patients, whereas in a case of placental abruption with a dead fetus has not had the expected effect. Very slight drop in blood pressure, increased maternal heart rate (without associated symptoms) and increased fetal heart rate was observed. It is expressed graphically and compare the behavior of different parameters evaluated in the case of normal delivery, and patients with hypersystole tachysystole.